2017
DOI: 10.1101/125617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypothesis: Hypoxia inducesde novosynthesis of NeuGc gangliosides in humans through CMAH domain substitute

Abstract: Immunotherapy is a growing field in cancer research. A privileged tumor-associated antigen that has received much attention is N-glycolyl (NeuGc) GM3. This ganglioside is present in several types of cancer, but is almost undetectable in human healthy tissues. However, its non-hydroxylated variant, NeuAc GM3, is abundant in all mammals. Due to a deletion in the human gene encoding the key enzyme for synthesis of NeuGc, humans, in contrast to other mammals, cannot synthesize NeuGc GM3. Therefore the presence of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Consequently, humans are only able to produce Neu5Ac de novo, although several studies have demonstrated that trace levels of Neu5Gc is present in human tissues [7][8][9][10]. It is thought that the Neu5Gc present in normal human tissue may come from dietary sources such as red meat and dairy products [10,11], although novel pathways have been proposed that may reactivate the defective CMAH protein under certain conditions [12]. Neu5Ac is present in every human cell type, and it is involved in cell-cell adhesion, signalling and immunity, discriminating 'self from 'non-self ' [13].…”
mentioning
confidence: 99%
“…Consequently, humans are only able to produce Neu5Ac de novo, although several studies have demonstrated that trace levels of Neu5Gc is present in human tissues [7][8][9][10]. It is thought that the Neu5Gc present in normal human tissue may come from dietary sources such as red meat and dairy products [10,11], although novel pathways have been proposed that may reactivate the defective CMAH protein under certain conditions [12]. Neu5Ac is present in every human cell type, and it is involved in cell-cell adhesion, signalling and immunity, discriminating 'self from 'non-self ' [13].…”
mentioning
confidence: 99%